2022
DOI: 10.3390/sym14071401
|View full text |Cite
|
Sign up to set email alerts
|

A Scaled Dai–Yuan Projection-Based Conjugate Gradient Method for Solving Monotone Equations with Applications

Abstract: In this paper, we propose two scaled Dai–Yuan (DY) directions for solving constrained monotone nonlinear systems. The proposed directions satisfy the sufficient descent condition independent of the line search strategy. We also reasonably proposed two different relations for computing the scaling parameter at every iteration. The first relation is proposed by approaching the quasi-Newton direction, and the second one is by taking the advantage of the popular Barzilai–Borwein strategy. Moreover, we propose a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…where δ ∈ (0, 0.5) and σ ∈ (δ, 1) are constants. According to the search direction (30) and the Wolfe conditions ( 31) and ( 32), we present the explicit steps of the (CGCG) technique, as follows. Now, we present some numerical facts relating to the above parameters, allowing us to discuss the global convergence and descent properties of the CGCG method.…”
Section: Algorithm 4 Cgcg-hz Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…where δ ∈ (0, 0.5) and σ ∈ (δ, 1) are constants. According to the search direction (30) and the Wolfe conditions ( 31) and ( 32), we present the explicit steps of the (CGCG) technique, as follows. Now, we present some numerical facts relating to the above parameters, allowing us to discuss the global convergence and descent properties of the CGCG method.…”
Section: Algorithm 4 Cgcg-hz Algorithmmentioning
confidence: 99%
“…Additionally, CG parameters have shown remarkable superiority in solving problems involving systems of nonlinear equations (see, for example, [26][27][28][29][30][31][32][33][34][35]). According to previous successful uses of CG techniques to solve different applications problems, many authors have adapted CG methods such that they are capable of dealing with image restoration problems (see, for example, [25,[35][36][37][38][39][40][41][42][43]).…”
Section: Introductionmentioning
confidence: 99%
“…The authors proved the global convergence of the scheme under mild assumptions. Only recently, Alhobaiti et al [ 51 ] proposed two scaled DY-type algorithms for solving ( 14 ), where two different approaches were applied to compute the scaling parameter. The authors also showed that both methods satisfy ( 7 ) irrespective of the line search strategy used.…”
Section: Introductionmentioning
confidence: 99%